If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5 + -2x) = 0 (5 * ln + -2x * ln) = 0 (5ln + -2lnx) = 0 Solving 5ln + -2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(5 + -2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Add '2x' to each side of the equation. -2x + 2x = -5 + 2x Combine like terms: -2x + 2x = 0 0 = -5 + 2x Simplifying 0 = -5 + 2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4y-5=12+8y | | 16b=22c | | 16a=24b | | 2x+5=-1.8x-2.5 | | (6a+1)x(2a+3)=xa^2+ya+z | | 7x-6/8=5x-4 | | (x-4)=10 | | f(X)=5x(X-1)(x+1)+5x | | if(X)=5x(X-1)(x+1)+5x | | xy+zt-xz+yt=3 | | xy+zt+xz-yt=25 | | 2.5x+5=-1.8x-2.5 | | 2x+5=-1.8-2.5 | | cos(8x)-cos(6x)=0 | | 7(x+5)=-35 | | 2(2x)+2(7)-3(x)-3(9)=3(5) | | x^2-4/4=3 | | sinx/sin5x | | y=((480/((350/y)-5)-10 | | cos5x/cosx | | 4x^2-94x+432=0 | | y=((480/((350/y)-5))-10 | | mx^2-(2m+3)x+m+2=0 | | -(a-2b)/8-2a-5(b-3a)/12 | | G(y)/G(y)=k | | -11x-18=13x-90 | | 3-9x=15x+24 | | 3m+6=2(m+1) | | 2(2x+7)-3(x-9)=15 | | 3x^2/24= | | 3x^2-24= | | ((3u^2v^4)^(-4))((4u^(-3)v^3)^3)/(3u^2v^(-3))^(-2) |